2008
DOI: 10.1073/pnas.0802676105
|View full text |Cite
|
Sign up to set email alerts
|

Hopping of a processivity factor on DNA revealed by single-molecule assays of diffusion

Abstract: Many DNA-interacting proteins diffuse on DNA to perform their biochemical functions. Processivity factors diffuse on DNA to permit unimpeded elongation by their associated DNA polymerases, but little is known regarding their rates and mechanisms of diffusion. The processivity factor of herpes simplex virus DNA polymerase, UL42, unlike ''sliding clamp'' processivity factors that normally form rings around DNA, binds DNA directly and tightly as a monomer, but can still diffuse on DNA. To investigate the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 34 publications
4
60
0
2
Order By: Relevance
“…There is evidence that processivity subunits of other herpesviruses play roles in gene expression, especially late in infection (17,38). It has recently been shown that UL42 diffuses on DNA by a "hopping" rather than a "sliding" mechanism (21). It was speculated that hopping could permit movements of UL42 around proteins bound to DNA, which in turn could be beneficial for a role for UL42 in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that processivity subunits of other herpesviruses play roles in gene expression, especially late in infection (17,38). It has recently been shown that UL42 diffuses on DNA by a "hopping" rather than a "sliding" mechanism (21). It was speculated that hopping could permit movements of UL42 around proteins bound to DNA, which in turn could be beneficial for a role for UL42 in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to observe, in real time, interactions of a single protein with a single DNA molecule allows for the detection of transient intermediates and kinetic details that are difficult to obtain with ensemble-averaging biochemical assays. Single-molecule techniques have been used to study diffusion of a variety of proteins along DNA, such as transcription factors (12,13), DNA repair factors (14,15), processivity factors (16,17), RNA polymerases (18)(19)(20), and restriction enzymes (21). In this report, we present single-molecule imaging experiments that visualize the interaction of individual T7 DNA polymerases with DNA, demonstrate that the protein complex diffuses along duplex DNA, and show that a change in the diffusional mode of T7 DNA polymerase is mediated by the binding of its processivity factor, thioredoxin.…”
mentioning
confidence: 99%
“…With this platform, dynamics of many single-molecule proteins have been uncovered. These include dynamics of single-protein polymers along DNA (Greene & Mizuuchi, 2002;Han & Mizuuchi, 2010;Tan et al, 2007) and one-dimensional diffusion of many DNA-binding protein molecules, for example, a base-excision DNA-repair protein along DNA (Blainey et al, 2006;Etson et al, 2010;Kochaniak et al, 2009;Komazin-Meredith et al, 2008;Tafvizi et al, 2011). A comparison of one-dimensional diffusion constants as a function of protein size with theoretical predictions indicates that DNA-binding proteins undergo rotation-coupled sliding along the DNA helix (Blainey et al, 2009).…”
Section: Platforms With Continuous Buffer Flowmentioning
confidence: 99%